Burden of Primary Biliary Cholangitis Among Inpatient Population in the United States. Issue 3 (28th January 2019) - Shahab, Omer; Sayiner, Mehmet; Paik, James; Felix, Sean; Golabi, Pegah; Younossi, Zobair M.
Abstract : Primary biliary cholangitis (PBC) is an autoimmune liver disease that can lead to cirrhosis and liver failure. Our aim was to assess the recent trends in the mortality rates and health care utilization of patients with PBC seen in the inpatient setting in the United States. We used the National (Nationwide) Inpatient Sample data (2005‐2014). The study population included adults with PBC, using International Classification of Diseases, Ninth Revision codes. Trends in PBC‐related discharges, total charges, length of stay (LoS), and in‐hospital mortality were evaluated. Hierarchical generalized linear models were performed for determining predictors of mortality and total hospital charges. Between the study years of 2005 and 2014, a total of 22, 665 hospitalized cases with PBC were identified (mean age 63 years; 84% female, 76% white). The number of PBC‐related discharges increased from 3.24 per 100, 000 in 2005 to 3.68 per 100, 000 in 2014, with an average annual increase of 1.4% (95% confidence interval [CI]: 0.4%‐2.4%). Fifty‐seven percent had Medicare as their primary payer, 37% had cirrhosis, and 1.3% had hepatocellular carcinoma. Between 2005 and 2014, the average total charges for PBC increased from $53, 901 to $57, 613 (annual percent change [APC], 1.7%; 95% CI: −0.2%‐3.5%), LoS decreased from 6.9 days to 5.4 days (APC, −2.2%; 95% CI: −3.2% to −1.1%), and mortality rate decreased from 3.8% to 2.8% (APC, −5.4%; 95% CI: −8.4% to −2.4%). Multivariable analysis revealed that ascites were independently associated with increased risk of in‐hospital mortality (odds ratio: 1.77; 95% CI: 1.50‐2.08), increased charge (percent change: 22.5%; 95% CI: 18.6%‐26.7%), and increased LoS (percent change: 29.7%; 95% CI: 25.7%‐33.9%). Conclusion: The number of PBC cases has increased in recent years. Mortality and LoS have decreased, and the total charges have remained the same.